2007
DOI: 10.1163/156939307780616847
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Tensile Strength of Vinyl Ester Composites Cured by Microwaves

Abstract: In the previous investigation, it was found that the difference in Young's modulus, ultimate tensile strength and yield strength between microwave cured vinyl ester particulate composites and those cured under ambient conditions is minimal provided low power microwaves are combined with short duration of exposure. The results also show that microwave cured composite samples will result in smaller shrinkage with the similar values of mechanical properties mentioned above than those samples cured under ambient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A Shimadzu tensile testing machine was used for the lap shear test. A load range of 2000 N and a load rate of 600 N per minute were selected for the test [13][14][15][16]. Figure 7 shows the lap shear strength of PS/GF (33%) joined by a fixed frequency microwave facility in a slotted rectangular waveguide.…”
Section: Casementioning
confidence: 99%
“…A Shimadzu tensile testing machine was used for the lap shear test. A load range of 2000 N and a load rate of 600 N per minute were selected for the test [13][14][15][16]. Figure 7 shows the lap shear strength of PS/GF (33%) joined by a fixed frequency microwave facility in a slotted rectangular waveguide.…”
Section: Casementioning
confidence: 99%
“…SLG is cheap and commonly used in a variety of manufacturing applications because of their unique properties, which include extreme heat resistance and high compressive strength. Many previous studies had reported the improvement in the mechanical properties of vinyl ester resin reinforced with SLG [4,[5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%